2017
DOI: 10.1007/s13555-017-0197-y
|View full text |Cite
|
Sign up to set email alerts
|

HPV-47-Induced and Tattoo-associated Verrucae Planae: Report of a Case and Review of the Literature

Abstract: The human papillomavirus (HPV), of which more than 200 different types have so far been identified, is an infectious disease impacting skin and mucous membranes. Several genera exist with distinct clinical impact. However, with ornamental tattoos increasing in popularity, a number of mostly cutaneous side effects have also been reported, such as infections, allergic reactions, or even a rise of malignant tumours within the tattoo. We report the first case of a β1-HPV-type infection in cutaneous lesions in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…This study also indicates that tattooing can be a mode of human immunodeficiency virus transmission [22]. Moreover, there has been an incident of human papilloma virus transmission during semi-permanent makeup [26], while Mycobacterium abscessus and fungus coinfection took place at another makeup tattoo parlor [27].…”
Section: Cases Of Adverse Side Effects In Foreign Countriesmentioning
confidence: 58%
See 1 more Smart Citation
“…This study also indicates that tattooing can be a mode of human immunodeficiency virus transmission [22]. Moreover, there has been an incident of human papilloma virus transmission during semi-permanent makeup [26], while Mycobacterium abscessus and fungus coinfection took place at another makeup tattoo parlor [27].…”
Section: Cases Of Adverse Side Effects In Foreign Countriesmentioning
confidence: 58%
“…Notably, the practitioner is also highly susceptible to contracting an infection from patients when performing the service. Indeed, bacterial infections such as syphilis, leprosy, Mycobacterium tuberculosis, and atypical Mycobacterium tuberculosis, as well as viral infections such as hepatitis B, hepatitis C, human immunodeficiency virus, human papillomavirus, varicella, and fungal infection have been reported [26,41]. A reporting system, implemented by the Korea Disease Control and Prevention Agency, is designed to detect and prevent the spread of hepatitis C during illegal procedures performed by non-qualified practitioners [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the infection may have been a result of contamination from the instruments, inks, or tattooist's saliva 9 . Interestingly, β1-HPV–type infection in cutaneous lesions of verrucae planae near a tattoo have also been reported in healthy, immunocompetent individuals 9 . Additionally, our patient has atopic dermatitis, which has only been reported once in association with AEV in a patient who had AEV lesions after cyclosporine therapy for atopic dermatitis 10 …”
Section: Discussionmentioning
confidence: 68%
“…An interesting manifestation of AEV was noted in our patient, who reported that after receiving a tattoo on his neck, pre-existing lesions spread along the distribution of the tattoo, suggesting autoinoculation. However, it is also possible that the infection may have been a result of contamination from the instruments, inks, or tattooist's saliva 9 . Interestingly, β1-HPV–type infection in cutaneous lesions of verrucae planae near a tattoo have also been reported in healthy, immunocompetent individuals 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The relative paucity of reports of similar SK-like lesions localized to tattoo markings underscores the novelty of this case. Most similarly published reports have involved verruca vulgaris associated with tattoos 4, 5…”
Section: Discussionmentioning
confidence: 99%